Territorial marketing applied to the Kenitra region for the attractiveness of FDI in the automotive sector - ATEILAH , RAJAE; MANSOURI , ZAHRA (Revue Internationale des Sciences de Gestion, 2024)
This article aims to apply to the Gharb Chrarda Ben Ihssen region the territorial marketing approach aimed at attracting foreign direct investments to the automobile sector, while recalling its theoretical foundations and their implications. The aim is to analyze the attractiveness and dynamics of FDI to the automotive sector in this region, emphasizing aspects relating to the investment climate. Thanks to an overview of the theoretical and empirical literature we will specify an econometric model, which relates incoming FDI flows with the variables (including in particular those representative of the hypotheses put forward) from the literature. we will consider on the one hand, foreign companies established in the Kenitra region whose field of activity is the automobile sector on the other hand, territorial marketing as being a determining tool of the territorial policy and offer which attracts plus foreign investors, On the one hand we will start with some definition of territorial marketing as a new practice with innovative tools and techniques allowing a diagnosis of the strengths and weaknesses of the territory, in our case the region of Kenitra , in order to understand why this region is attractive for FDI, especially the automotive sector. From thes alements, a SWOT analysis will allow us to identify the strengths and weakness of the Gharb chrarda ben Ihssen region for the city of kenitra, then to define why this region in terms of territorial offer, promotional actions and choice of positioning is a destination for forgien investir in the automotive sector